2016
DOI: 10.18632/oncotarget.12849
|View full text |Cite
|
Sign up to set email alerts
|

Correction: 5-Fluorouracil-induced RNA stress engages a TRAIL-DISC-dependent apoptosis axis facilitated by p53

Abstract: Present: Due to a processing mistake during production, the original correction notice issued for this article contained two errors. Specifically, it provided corrections to supplementary figure S2, but should have provided corrections to supplementary figure S3. It also provided incorrect figure captions for Figure 2B

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2017
2017

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…Both cell death and cellular senescence are important responses to stress-associated stimuli. It was demonstrated that 5-FU exerts anticancer effects mainly by inhibiting tumor cell proliferation, activating Bax and P53, and/or caspase-dependent mechanism [ 74 , 75 , 76 , 77 , 78 , 79 , 80 , 81 , 82 ]. Annexin V/Propidium iodide (PI) staining assay is commonly applied to discern necrotic cells and apoptotic cells, further to quantify apoptosis.…”
Section: Resultsmentioning
confidence: 99%
“…Both cell death and cellular senescence are important responses to stress-associated stimuli. It was demonstrated that 5-FU exerts anticancer effects mainly by inhibiting tumor cell proliferation, activating Bax and P53, and/or caspase-dependent mechanism [ 74 , 75 , 76 , 77 , 78 , 79 , 80 , 81 , 82 ]. Annexin V/Propidium iodide (PI) staining assay is commonly applied to discern necrotic cells and apoptotic cells, further to quantify apoptosis.…”
Section: Resultsmentioning
confidence: 99%